Language Variation and Identity Negotiation in College Students’ Social and Digital Communication - Ahmad Bayu Fathoni; Krisdian Aulia Putri; Nasywa Abril Maulida Zein; Nazriela Nur Syahbani; Suparwoto Sapto Wahono (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2026)
This study examines the dynamics of language use among students from a sociolinguistic perspective, particularly within campus and digital communication contexts. As a multicultural and technology-driven environment, the campus provides a space where diverse linguistic practices emerge and reflect students’ social interaction and communication strategies. The objective of this study is to analyze how language variation develops and to explore its relationship with identity negotiation among students. This study employs a literature review method by analyzing 12 relevant scientific articles related to sociolinguistics, language variation, and digital communication. The analysis focuses on identifying patterns of language use and the factors influencing students’ linguistic choices in both face-to-face and online interactions. The findings reveal that language variation among students emerges through continuous social interaction and exposure to digital media. Common forms include code-switching, code-mixing, dialect variation, slang, and lexical innovation, which are influenced by social relationships, cultural background, peer interaction, and technological exposure. Furthermore, language variation is closely related to identity negotiation, as students actively construct and express their social identities through context-dependent linguistic choices. Overall, this study highlights that language use among students functions not only as a means of communication but also as a dynamic social practice shaped by ongoing social and technological changes.